Cushing's Disease with Cognitive Impairment Manifesting Post-Resection: A Case Report - Hala H. Mosli, (Journal of King Abdulaziz University: Medical Sciences, 2023)
In 2007, a 61-year old woman presented with clinical features of Cushing's Disease Syndrome. She underwent a diagnostic workup and was diagnosed with adrenocorticotropic hormone-producing pituitary adenoma, which was subsequently removed. Following surgery, the patient showed little recovery from her presenting neurocognitive symptoms, raising the question as to the effect of long-term steroids on cognition, mood and behavior, and the potential for reversal of these effects.